PILGRIMAGE AND RELIGIOUS SHRINES OF THE REPUBLIC OF UZBEKISTAN: TYPOLOGY, FEATURES AND STATE PROTECTION POLICY - Mirsaatov Jasur (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the pilgrimage and religious sites of the Republic of Uzbekistan in the context of their role in the development of the tourism industry. Using a confessional approach, a classification of monuments relating to the Islamic, Christian, Buddhist, Jewish, and Zoroastrian traditions, which form the country's unique multi-confessional heritage, is conducted. Particular attention is paid to state policy for the preservation of religious monuments: the current legal framework is analyzed, key institutional governance mechanisms are identified, and forms of international cooperation are considered. It is established that a number of Uzbekistan's sites are included on the UNESCO World Heritage List, enhancing their international tourist appeal. The study identifies the characteristic features of Islamic shrines, including their connection with the tradition of "scholarly pilgrimage" and Sufi spiritual heritage. It is concluded that confessional diversity is an important competitive advantage for the country in the global religious tourism market.